Keanekaragaman Anggrek Tanah di Kawasan Hutan Lindung Lemor, Lombok Timur Nusa Tenggara Barat - Inggit Puji Astuti; I Dewa Putu Darma (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Lemor protected forest is one area of lowland tropical rain forest in Lombok island. Based on the results of vegetation analysis, in this area saves many species of tree stands, shrub, vines, and herbaceous plants which make up the ground floor of the forest. One of the plants which makes up the ground floor of the forest is a kind of ground orchids. These research was aimed to investigate the diversity of any varieties in Lemor protected area as there has no information yet about the diversity of ground orchids stored in this area. The inventory to identify the diversity of ground orchids in that area was done exploratively by investigating the entire area, notes, and make specimen from that species as the materials identification. Identification was done by reffering to herbarium specimens saved in Bogoriense Herbarium, and life plant in Bogor Botanical Gardens, as well as aby literatures related to orchids. Some types of orchids there are genus Corymborkis (1 species), genus Nervillia (3 species), and genus Tropidia (2 species).